Respiratory Control : Central and Peripheral Mechanisms - Frazier, Donald T.; Revelette, W. Robert; Dekin, Michael S.; Speck, Dexter F., 1955- (Book collections on Project MUSE., 1993)
Understanding of the respiratory control system has been greatly improved by technological and methodological advances. This volume integrates results from many perspectives, brings together diverse approaches to the investigations, and represents important additions to the field of neural control of breathing. Topics include membrane properties of respiratory neurons, in vitro studies of respiratory control, chemical neuroanatomy, central integration of respiratory afferents, modulation of respiratory pattern by peripheral afferents, respiratory chemoreception, development of respiratory contr.